Revitalizing a mentoring program for academic librarians - Farmer, Diana; Stockham, Marcia G.; Trussell, Alice (My University, 2009)
Many new employees naturally seek out coworkers and informal advisors as a way of learning about their new positions and organizations. However, a formalized mentoring program is a way to meet the needs of new employees and effectively impart the information and advice in a coordinated, ongoing process. This paper focuses on the process of revitalizing a formalized mentoring program in an academic library. Included are details of the process developed by one institution, an extensive bibliography, sample checklists, and assessment tools.
Keywords: Mentoring; Academic librarians; Promotion; Tenure; Library; Professional development